Lipids and Fatty Acids of Antarctic Giant Fish - Yoshimi OHNO; Ikuya YANO; Osamu WAGURI (National Institute of Polar Research, 1976)
Lipid and fatty acid composition of skeletal muscle of antarctic giant fish (Dissostichus mawsoni NORMAN) were examined. Thin-layer and column chromatography showed that the neutral lipids made up 98% of the total lipids, while phospholipids only 2% or less. The direct gas chromatographic analysis of triglycerides revealed that the major molecular species were C_, C_, C_, C_, C_ and C_, that their fatty acid composition resembled the other edible oil of marine fishes, and that the major components were C_, C_, C_, C_, C_, C_ and C_ with smaller amounts of C_, C_ and C_. The positional distributions of fatty acid on glycerides was also determined by lipase and phospholipase A_2 treatment and it showed that saturated and monoenoic fatty acids occurred in 1 position, while polyunsaturated fatty acids in 2 position, exclusively.